2007
DOI: 10.1002/hed.20705
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of reconstructive procedures in primary versus secondary mandibular reconstruction

Abstract: Success in secondary mandibular reconstruction could be achieved utilizing a range of osseous free flaps, and there was no increased rate of complications compared with primary mandibular reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 35 publications
4
23
0
1
Order By: Relevance
“…However, Andrade et al showed no change in complication rate comparing 39 secondarily reconstructed mandibles (49% for fistulae or exposed hardware) to 110 primary reconstructions. 7 Osteocutaneous flaps in this series had longer operative times and more frequent tracheostomy on discharge, but with a lower fistula rate than soft tissue flaps. The higher rate of delayed decannulation may be due to the soft tissue bulk of skin paddles associated with the fibula free flap or edema due to the lengthy operative time.…”
Section: Discussionmentioning
confidence: 94%
“…However, Andrade et al showed no change in complication rate comparing 39 secondarily reconstructed mandibles (49% for fistulae or exposed hardware) to 110 primary reconstructions. 7 Osteocutaneous flaps in this series had longer operative times and more frequent tracheostomy on discharge, but with a lower fistula rate than soft tissue flaps. The higher rate of delayed decannulation may be due to the soft tissue bulk of skin paddles associated with the fibula free flap or edema due to the lengthy operative time.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, there were only five papers (99,114,154,180,183) in which the type of flap could not be related to non-union.…”
Section: Non-unionmentioning
confidence: 99%
“…The four main flap donor sites were the fibula with 6178 flaps (8, 12, 16-18, 20-22, 24, 26-28, 32-55, 57-59, 61-64, 66-, 79, 81-83, 85, 87-89, 93, 94, 96-104, 106, 108 -131, 131, 133, 135, 137-141, 143, 145-154, 156, 158-169, 171-175, 179-184, 186-193, 195, 196, 198-200, 202-207, 209, 210, 212-216, 218-223, and 225-229), the iliac crest with 1380 flaps (8, 12-15, 17-20, 26, 29,31, 36, 38, 41, 45, 48, 50, 53, 54, 57-60, 62, 63, 65, 67, 72, 74, 75, 77, 79, 83, 84, 86, 87, 92, 96, 98, 99, 102, 105, 112-115, 121, 132, 149, 151, 152, 155, 157, 158, 161, 168, 170, 171, 173, 174, 177, 178, 181, 183, 186, 201, 211, 212, 216, 219, 227), composite radius with 1127 flaps (8, 10-12, 17, 20, 23, 25, 30, 32, 33, 48, 50, 56, 62, 67, 72, 75, 77, 80, 85, 87, 91, 93, 95, 96, 98, 99, 104, 113, 114, 133, 150, 152 154, 165, 176, 180, 183, 185, 203, 213, and scapula with 709 flaps (8,9,12,14,17,26,32,45,46,48,50,53,58,59,63,67,70,74,77,85,87,90,93,96,99,113,114,134,136,142,144,151,156,169,172,189,191,194,…”
Section: Flap Optionsmentioning
confidence: 99%
“…However, the widespread availability of magnetic resonance angiography (MRA), which provides highly detailed information on the lower limb vasculature without the morbidity of conventional angiography, has resulted in it being routinely adopted in many centers . In cases in which the imaging is not favorable and fibula flap harvest is inadvisable, osseous reconstruction of the mandible can still be achieved using an alternative donor site . In practice, the choice depends on the experience and preference of the surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the choice depends on the experience and preference of the surgeon. When other composite free flaps are deemed inappropriate or are not within the skillset of the reconstructive surgeon, soft tissue reconstruction of the mandible has been reported . This is associated with a less satisfactory aesthetic and functional outcome .…”
Section: Introductionmentioning
confidence: 99%